Situating self-precarisation: cultural production, subjectification and resistance in kleines postfordistisches Drama's Kamera Läuft!. (1st April 2017) - ,
Abstract : In the current conditions of governance, cultural producers seem to willingly subordinate themselves to the dispositions of power, by aligning to the neoliberal model of labour through the adoption of entrepreneurial self-practices. This article explores how the concept of 'self-precarisation' is debated and negotiated through Kamera Läuft! ( Camera Rolling! ), a video project made in 2004 by the Berlin-based group kleines postfordistisches Drama (Small postFordist Drama). Situating the everyday lived experiences of cultural producers in a public sphere, kleines postfordistisches Drama problematises the possibilities for critical agency and collective resistance under the conscious and voluntary acceptance of precarious labour in the 21st century.